Kinetika Reaksi Sintesis Hidroksiapatit Menggunakan Metode Presipitasi Dengan Pencampuran Langsung - Fadhil Mubarak; Ahmad Fadli; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite is a ceramic material that has chemical composition and crystal structure similar to the human bone, then it iscompatible to use as bone implant. The most one of method that used production of hydroxiapatite is precipitation method. The aim of this research is to determine the kinetics reaction of the synthesis of hydroxyapatite using one drop precipitation method. The research was started with stirred 8.27 grams of CaO in 200 ml of aquadest.Then added with 1,8 M phosphoric acid in to while heated with a temperature variation of 40°C, 50°C and 60°C and stirring rate of 300 rpm. The solution in reactor were taken every 10 minutes by 20 ml volume. Further samples were filtered with filter paper, and then the filtrate was analyzed by complexometric titration. The results showed that the reaction followed pseudo second order equation. Constans of reaction increases with increasing temperature following Arrhenius equation, at stirring rate of 300 rpm obtained k = 1,97e- (13194,4 / RT).Key words : ceramic, hydroxyapatite, reaction kinetic, precipitation